Epidemiology of trauma and orthopaedic surgery in two hospitals from Southern Brazil - Cousin, Ewerton (2022)
This study evaluates the profile of patients undergoing trauma and orthopedic surgery. A cross-sectional research was conducted with all patients undergoing trauma and orthopedic surgery in two state reference center hospitals in the city of Rio Grande, Rio Grande do Sul, Brazil, in 2014. Data were collected from patient medical records, totaling 1,791 surgeries. Results showed that 57.7% of patients were men, with an mean age of 46.1 years (SD = 22.2). Surgeries were performed predominantly in the lower limbs (60.6%), the most common injury was fractures (61.1%). Most injuries were traumatic (66.3%), and falls accounted for 54.2% of these causes. The median length of hospitalization was three days (mean = 5.8). These findings may contribute to a better understanding of the type of service provided, helping in the management, planning and direction of public policy.